Role of methotrexate in ectopic pregnancy - Pandya, Munjal J.; Ninama, Neha V.; Thummar, Chirag V.; Patel, Meet K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Ectopic pregnancy is an acute emergency in obstetric if not timely diagnosed and timely treated. Ectopic pregnancy is leading cause of death in first trimester. Ectopic pregnancy can be managed surgically or medically. Medical management with Methotrexate administration avoids anesthesia in surgery, is cost effective and also offers success rate comparable to surgical management. Aim and objectives were to study the role of methotrexate in ectopic pregnancy Methods: This will be a retrospective observational study conducted in Obstetrics and Gynecology department of AMC MET medical college. Study group constitutes of 30 females with ectopic pregnancy. Preliminary blood investigations, ultrasonography and beta-human chorionic gonadotropin (b-hcg) level will be tested. Patients will be treated with single dose of methotrexate 50 mg/M2. Follow up b-hcg level will be done after 48 hours. Response and tolerance to methotrexate will be monitored. Results: The success rate of methotrexate therapy in our study was 83.33% (n=25) and 16.66% (n=5) required surgical intervention with tubal ruptured and abdominal pain. Conclusions: Methotrexate treatment of ectopic pregnancies is safe and effective with no major side effects. It has the advantage of tubal conservation and saves patients from surgical intervention.